Flexible query answering systems 9th International Conference, FQAS 2011, Ghent, Belgium, October 26-28, 2011 Proceedings - Christiansen, Henning; Tré, Guy; Yazici, Adnan; Zadrozny, Slawomir; Andreasen, Troels; Larsen, Henrik Legind (LNCS sublibrary. SL 7, Artificial intelligence, 2011)
This book constitutes the refereed proceedings of the 8th International Conference on Flexible Query Answering Systems, FQAS 2011, held in Roskilde, Denmark, in October 2011. The 43 papers included in this volume were carefully reviewed and selected from numerous submissions. The papers are organized in topical sections on logical approaches to flexible querying, fuzzy logic in spatial and temporal data modeling and querying, knowledge-based approaches, multimedia, data fuzziness, reliability and trust, information retrieval, preference queries, flexible querying of graph data, ranking, ordering and statistics, query recommendation and interpretation, as well as on fuzzy databases and applications (8 papers presented in a special session).